Expansive Soil Embankment Filling and Cutting Treatment Technology: A Systematic Review - Zhen Huang; Hang Shi; Wei Zhang; Shaokun Ma; Feng Gao; Min Ma (Advances in Materials Science and Engineering)
The characteristics of expansive soil, including over consolidation, swelling-shrinkage, fissures, and strength attenuation, can cause potential hazards in road construction, which are mainly manifested as subgrade swelling-shrinkage deformation and slope collapse. Effective treatment can not only ensure long-term subgrade stability but also reduce investment costs and environmental impact. In this review, the current development status of embankment filling and cutting slope treatment technology in expansive soil areas were summarized, and the classification standards of expansive soil filler, moisture retention, and antiseepage technology were described. Then, the utility of chemical, physical, biological, and solid waste modification materials in improving the engineering characteristics of core-filled expansive soil was discussed, and the cost and technical characteristics of these modification technologies were compared and analysed. Next, the application of rigid and flexible support technology in the treatment of cutting slope collapse was analysed, and the advantages and disadvantages of rigid and flexible supports were summarized. Finally, the development direction of expansive soil subgrade treatment technology was discussed. This review includes a summary of the treatment methods of highway subgrade in expansive soil areas and can provide a technical reference for treatment methods of expansive soil subgrade.